2017
DOI: 10.5005/jp-journals-10024-2167
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antifungal Effect of Chicory Extracts on Candida Glabrata and Candida Krusei in a Laboratory Environment

Abstract: Aim: This research has evaluated the extract's antifungal effects on Candida glabrata and Candida krusei in a laboratory environment. Materials and methods:In this research, to evaluate the antifungal effect and the minimal inhibitory concentration (MIC) determination of chicory extract, the Clinical and Laboratory Standards Institute (CLSI) was used. Candida glabrata and C. krusei funguses were procured from the Tehran Pasteur Institute; they were grown in the relative growing environment according to the req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Chicory (Cichorium intybus) is a plant that originated from the Iranian region and has been reported to have anti-fungal property [103]. The leaves of the chicory plant soaked in ethanol were tested against the candidiasis pathogen, Candida glabrata and Candida krusei [69]. From the study, it was found that C. krusei is more sensitive to the chicory ethanol extract compared to C. glabrata, as C. krusei growth was inhibited at a low concentration of 50 µg/mL, whereas growth of C. glabrata was inhibited at a concentration of 100 µg/mL.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chicory (Cichorium intybus) is a plant that originated from the Iranian region and has been reported to have anti-fungal property [103]. The leaves of the chicory plant soaked in ethanol were tested against the candidiasis pathogen, Candida glabrata and Candida krusei [69]. From the study, it was found that C. krusei is more sensitive to the chicory ethanol extract compared to C. glabrata, as C. krusei growth was inhibited at a low concentration of 50 µg/mL, whereas growth of C. glabrata was inhibited at a concentration of 100 µg/mL.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…From the study, it was found that C. krusei is more sensitive to the chicory ethanol extract compared to C. glabrata, as C. krusei growth was inhibited at a low concentration of 50 µg/mL, whereas growth of C. glabrata was inhibited at a concentration of 100 µg/mL. The anti-fungal activity of chicory leaves extract is due to the presence of compounds such as lactucin, lactucopicrin, deoxylactucin, and β-1,3-dihydrolactucin [69,104]. A similar study was conducted on both the Candida sp., and similar results were recorded [68].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…[43], chicory root extracts showed higher inhibitory effects on B. subtilis, S. aureus, and S. typhi than Micrococcus luteus and E. coli [51]. Eslami et al [52] and Badakhasann et al [53] reported that chicory extract had antifungal activity against Candida glabrata and Candida krusei, and due to its low cost, availability, and proper taste, may be an alternative to nystatin.…”
Section: Antibacterial Activity Of Chicory Root Extractsmentioning
confidence: 99%